Medicinal Properties of Black Cumin - Nasrulloyevna, Ne’matova Gulafruz (American Journal of Botany and Bioengineering, 2024)
In this article, we can learn about the medicinal properties of black cumin and its role in folk medicine. Also, through this article, we can learn about the use of different parts of black cumin, which have a natural beneficial effect on the human body, as well as the preparation of infusions and decoctions, unlike synthetic chemical drugs.